Study on Attitudes of Cancer Patients about Breaking Ways of Bad News: breaking ways of bad news - Karimi Rahjerdi , Ashraf; Nasiri , Bahareh; Shamshiri , Ahmad Reza (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: Giving bad news is an inevitable part of the medical profession. There are different opinions about telling the truth and giving bad news to patients in different cultures and societies. Thus, the purpose of this study was to investigate attitudes of cancer patients about methods of awareness of bad news. Materials and Methods: The study was cross-sectional research that has been done on a sample of 160 people of cancer patients. This study used a questionnaire that its validity was confirmed by communication sciences professors and medical experts. The reliability of the questionnaire and Cronbach’s alpha for all items of the questionnaire was 95 percent in estimating the validity of the questionnaire was determined that all questions were significantly correlated. SPSS software, regression analysis, and Fisher test were used. Ethical Considerations: In this study, verbal informed consent of participants was obtained followed by an explanation about the purpose of the study, anonymity, and confidentiality of patients’ information. Findings: In this study investigated 160 patient points of view.37.5% of participants were men and 62.5 of them were women (18-77years). The results show that 57.7 % of patients agreed with a historical approach, 78.8% of them agreed with the direct source style and 94.4% agreed with the informal style of giving information. 18.1% of patients disagree with the flow of the companions of patients of the disease. Conclusion: Findings indicates on better breaking of the bad news to the patients with a historical approach and telling to the patient by physician, directly. *Corresponding Author: Ashraf Karimi Rahjerdi; Email: rahjerdi632@gmail.com; ORCID: https://orcid.org/0000-0002-9329-3206 Please cite this article as: Karimi Rahjerdi A, Nasiri B, Shamshiri AR. Study on Attitudes of Cancer Patients about Breaking Ways of Bad News.Bioeth Health Law J. 2021; 1:1-5: (e15). http://doi.org/10.22037/bhl.v1i1.38165